2022
DOI: 10.3389/fgene.2022.844747
|View full text |Cite
|
Sign up to set email alerts
|

Oar-miR-432 Regulates Fat Differentiation and Promotes the Expression of BMP2 in Ovine Preadipocytes

Abstract: The fat tail is a unique characteristic of sheep that represents energy reserves and is a complex adaptative mechanism of fat-tailed sheep to environmental stress. MicroRNA plays a significant role as regulators at the posttranscriptional level, but no studies have explained the molecular mechanisms of miRNA which regulate fat deposition in sheep tails. In this study, mRNA and miRNA analysis examined tail fat tissue from three Hu fat-tailed and three Tibetan thin-tailed sheep. After aligning to the reference s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…For example, candidate genes PDGFD, BMP2, TBXT, and HOXB13 were detected by selective sweep or GWAS analysis 15,[18][19][20][21][22] , which are involved in preadipocyte differentiation and associated with fat deposition in sheep 5,23 . In addition, many candidate genes, microRNA and lncRNA were identified by transcriptomic and proteomic approaches, such as PGDFD, BMP2, IL6, ADIPOQ, miR-432, most of which are related to fat deposition and lipid metabolism [24][25][26][27][28] . Those studies revealed plenty of candidate genes and regulatory elements associated with the fat tail phenotype and suggested a complex genetic mechanism for the fat tail phenotype.…”
mentioning
confidence: 99%
“…For example, candidate genes PDGFD, BMP2, TBXT, and HOXB13 were detected by selective sweep or GWAS analysis 15,[18][19][20][21][22] , which are involved in preadipocyte differentiation and associated with fat deposition in sheep 5,23 . In addition, many candidate genes, microRNA and lncRNA were identified by transcriptomic and proteomic approaches, such as PGDFD, BMP2, IL6, ADIPOQ, miR-432, most of which are related to fat deposition and lipid metabolism [24][25][26][27][28] . Those studies revealed plenty of candidate genes and regulatory elements associated with the fat tail phenotype and suggested a complex genetic mechanism for the fat tail phenotype.…”
mentioning
confidence: 99%
“…Then we detected the expression of oar-miR-432 and SIRT1 . The expression of oar-miR-432 was increased by oar-miR-432 mimics ( Jin et al, 2022 ). The result of the Western blot showed the expression of SIRT1 was inhibited by oar-miR-432 mimics ( Figures 3C,D , Supplementary Table S11 , Supplementary Figure S2 , Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sheep preadipocytes were isolated from the tail fat of a 70-day-old Hu sheep fetus by collagenase digestion. Preadipocyte transfection and culture were according to our previous method ( Jin et al, 2022 ). When the cell showed contact inhibition, we collected cells and extracted protein.…”
Section: Matericals and Methodsmentioning
confidence: 99%
“…Table S3. Sheep tails from a transcriptomic perspective: microRNA profiles [242][243][244][245][246][247][248][249][250][251][252][253][254]. Table S4.…”
Section: Supplementary Informationmentioning
confidence: 99%